Private Finance Initiative (PFI) For Road Projects In Uk: Current Practice With A Case Study - Dikmen, Seyyit Ümit; Akbıyıklı, Rıfat; Eaton, David (Svenciliste U Zagrebu, Fakultet Prometnih Znanosti, Vukeliceva 4, Zagreb, 10000, Croatia, 2011)
The long-term sustainable provision of new and high quality maintained road stock is vitally important, especially in times of economic constraint such as Europe is currently experiencing. The Private Finance Initiative (PFI) is one method of financing such large-scale, capital intensive projects. An important aspect of this form of financing projects is that the risks are borne not only by the sponsors but are shared by different types of investors such as equity holders, debt providers, and quasi-equity investors. Consequently, a comprehensive and heuristic risk management process is essential for the success of the project. The proposition made within this paper is that the PFI mechanism provides a Value-for-Money and effective mechanism to achieve this. The structure of this PFI finance and investment on a particular road project therefore enables all project stakeholders to take a long-term perspective. This long-term perspective is reflected in the mechanism of a case study of UK - Class A trunk roads which are examined in detail. This paper presents a novel solution to a modern dilemma.
Keywords: capital road projects; private finance initiative; project finance; structured finance; payment mechanisms; sermaye yol projeleri; özel finans girişimi; proje finansmanı; yapılandırılmış finans; ödeme mekanizmaları